Emergency Remote Early Childhood Teaching: A Temporary Setting or Contemporary Necessity? - Mahinay, Jasmine; Merin, Jewish (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
The COVID-19 pandemic and the protection of social distance between educators and learners have impacted all levels of education – significantly, early childhood. It has hindered activities carried out in a direct meeting and has forced education in the 2020-2021 school year to continue through emergency remote teaching. The study determined the fundamental structure of the views of early childhood educators on emergency remote teaching to reveal how they are thinking forward regarding their teaching skillset for either the continuity or change of education in the next school year. A phenomenological design of qualitative research was employed, and a local sample of 10 educators voluntarily informed the study. Through the interviews, five theme clusters emerged that reflected their 88 significant statements. The results evidenced to the extent that early childhood educators view emergency remote teaching as beyond being a temporary solution to learning when a pandemic threatens physical classes, but its potential to become a contemporary necessity is premature and highly dependent on how families will respond and how schools will proceed as a result of their response. Thus, further exploration of professional development topics is needed to support early childhood educators to teach in any situation moving forward.